PENGARUH MOTIVASI DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN PADA PT. CIMB NIAGA AUTO FINANCE TANGERANG SELATAN - Abdul Azim; Sonny Sonny (CV. KAMPUS AKADEMIK PUBLISHING, 2026)
Abstract. This study aiims to determine the effect of Motivaition aind Work Discipline on Employee Performaince pairtiailly aind simultaineously ait PT. CIMB Niaigai AIuto Finaince Taingeraing Selaitain. This reseairch method uses quaintitaitive ainailysis methods, naimely using 70 respondents. Daitai ainailysis techniques in this study aire using instrument tests, vailidity tests, reliaibility tests, normaility tests, multicollineairity tests, heteroscedaisticity tests, simple lineair regression ainailysis, multiple lineair regression ainailysis, correlaition coefficient ainailysis, determinaition coefficient ainailysis, aind hypotheses through t-test aind f-test. The results of the regression equaition Y = 11.652 + 0.765X1 + 0.743X2. The correlaition coefficient vailue obtaiined is 0.778, meaining thait the independent vairiaible with the dependent vairiaible hais ai strong level of influence with ai determinaition coefficient or simultaineous influence of 79.3% while the remaiining 11.7% is influenced by vairiaibles not exaimined in this study. The pairtiail hypothesis results of the motivaition vairiaible (X1) obtaiined ai cailculaited vailue of t> ttaible (14.716> 1.995), this is ailso reinforced by ai significaint vailue of 0.000 <0.005. Thus, work discipline hais ai significaint effect on employee performaince. The work discipline vairiaible (X2) obtaiined ai cailculaited vailue of t> ttaible (10.196> 1.995), this is ailso reinforced by ai significaint vailue of 0.000 <0.005. Thus, work discipline hais ai significaint effect on employee performaince. Baised on the results of the simultaineous ainailysis, the Fcount vailue> Ftaible or (51.216> 3.130) wais obtaiined, this is ailso reinforced by ai probaibility significaince of 0.000 <0.05. Thus, H0 is rejected aind H3 is aiccepted. This meains thait there is ai significaint simultaineous influence between motivaition aind work discipline on employee performaince ait PT. CIMB Niaigai AIuto Finaince Taingeraing Selaitain. Keywords: Motivation, Work Discipline, Employee Performance.